Demand Analysis for Non-Alcoholic Beverages Consumptin in the United States - Pokharel, Krishna Prasad (International Journal of Social Sciences and Management, 2016)
This research analyzes the demand for non-alcoholic beverages (non-diet carbonated beverages, diet carbonated beverages, non-carbonated caloric beverages, water, and unsweetened coffee and tea) in the United States using the first difference version of the Almost Ideal Demand System model. Five expenditure shares and prices demand equations for the non-alcoholic beverages are estimated using the Iterated Seemingly Unrelated Regression (ITSUR) and Full Information Maximum Likelihood (FIML) techniques. These two estimation techniques give similar results. Most of the products exhibit the consistent sign for the own and cross price elasticities as predicted by economic theory. Based on the expenditure elasticity, non-diet beverage is a luxury good (1.632) and the remaining goods have expenditure elasticity less than, which indicates that these products are necessities. These products are not weakly separable based on the regular and adjusted Wald tests. Moreover, seasonality has a positive impact on caloric beverages and water and a negative impact on the remaining products Int. J. Soc. Sci. Manage. Vol-3, issue-1: 38-46